Thermodynamic modeling of a novel solar powered quad generation system to meet electrical and thermal loads of residential building and syngas production. (1st November 2019) - Li, Z.X.; Ehyaei, M.A.; Kamran Kasmaei, H.; Ahmadi, A.; Costa, V.
Highlights: Proposition of a new integrated solar powered energy system for residential building application. Conduction of detailed energy and exergy analyses of the integrated system. Integrated system sizing based on residential energy needs. Abstract: This work deals with the proposal and thermodynamic modeling of an integrated solar powered energy system for residential building application. The main components of the system are: ( i ) A parabolic trough solar collector, ( ii ) An organic Rankine cycle driven by the collected solar energy and producing electricity, ( iii ) An electrolyzer unit producing hydrogen from the inlet water, ( iv ) A methanation unit producing methane from produced hydrogen and captured carbon dioxide, ( v ) A cooling/heat pump unit to supply the needs of the residential building, and ( vi ) A domestic hot water production system. A typical residential construction and data of the Bandar Abbas city, Iran, are considered in the simulations. Energy analysis includes evaluation of the number of 6 (parabolic trough solar collector + organic Rankine cycle) units as required to meet the energy needs. Results include the monthly averaged energy and exergy efficiencies, exergy destruction rates, and energy production and consumption of some components. Results include also the monthly averaged energy and exergy efficiencies of the integrated energy system. Apart from the results' dependence on the particular data considered, they clearly show that increasing complexity of the system, with the electrolyzer and the methanation units, increases the integrated system's efficiency. When comparing with its simpler configuration including only the organic Rankine cycle but not those units, energy efficiency increases from 6.0% to 8.3% (38% energy efficiency increase). Results show that the proposed integrated energy system is a viable solution when searching for higher efficiency residential buildings energy systems. Results also show that the adequate integration is the way to increase the overall energy and exergy efficiencies of the energy systems.